Beginning counsellors' experiences working with children who exhibit externalised behaviours. Issue 4 (7th October 2020) - Guest, Jessie D.; Wymer, Brooke C.; Deaton, Jennifer D.; Hipp, Christopher J.; Newton, Therese L.; Ohrt, Jonathan H.
Abstract: Counsellors who work with children exhibiting externalised behaviours may struggle to maintain therapeutic presence. Challenging client behaviours may trigger countertransference, thus influencing counsellors' presence in session. In this study, we examined the experiences of beginning counsellors working with children who exhibit externalised behaviours in counselling sessions. We used thematic analysis and identified six emergent themes related to countertransference.